The Effects of Credit Default Swaps on Analyst Forecasting Properties - Ekici, Emrah; Sottile, Pedro (Journal of Accounting and Finance, 2023)
This research studies the effect of credit default swaps (CDS), one of the most important financial innovations in recent times, on financial analysts’ forecast characteristics. We examine whether and how the revelation of private information in the CDS market, which often leads to public information disclosure and price discovery in other markets, affects analysts’ forecast characteristics. This research shows that analysts have more accurate and less dispersed cash flow forecasts for firms with CDS contracts. These findings are consistent with the predictions that financial analysts include the information revealed from the CDS market in their cash flow forecasts. Furthermore, we investigate the relation between CDS prices, CDS price changes, and analysts’ forecast properties and find that CDS prices and their changes are associated with analysts’ cash flow forecast accuracy and dispersion.